The Effectiveness of Using Project Methods in Improving Problem-Solving Skills - Nia Ifrila (Yayasan Adra Karima Hubbi, 2024)
This research is motivated by the learning process used is still teacher-centered, where learning activities still emphasize reading, writing, and arithmetic. Children have not been able to show a creative attitude in solving problems on their own. Children's curiosity about something new in children is still lacking. The purpose of this study is to test how effective the project method is in improving problem solving skills in Tk Aisyiyah Suliki Fifty City Regency. This study used a quantitative research approach with a quasi-experimental research design with a nonequivalent control group design type. The population in this study is the children of Aisyiyah Suliki Kindergarten, Fifty City Regency for the 2019/2020 academic year, consisting of 2 groups, namely B1 and group B2 which were sampled were group B1 as the experimental group while B2 as the control group. Data collection is carried out by providing pretest and post-test. The results of statistical data analysis that have been carried out, show that alternative hypotheses are H_a accepted. Alternative hypothesis (accepted because it is greater than, can be seen from the results obtained which is 0.73 with a significant level of 1% compared to n magnitude